Learners’ Attitudes in FLE (French as a Foreign Language) Toward a Foreign Culture - Ghellab, Halima (El Omda in Linguistics and Discourse Analysis, 2022)
Globalization affects all areas of life, especially teaching and learning in general. This requires teachers to reconsider their objectives in teaching and learning foreign languages, particularly when these languages are seen as the conscious or unconscious vehicle of a culture. Everyone agrees that culture now occupies a central place in the teaching-learning process. However, its teaching remains difficult due to its polymorphic, dynamic, and evolving nature. Indeed, the declared goal of every teacher is that the teaching of cultures should develop learners’ cultural competence, promoting intercultural communication between individuals from different cultures. But how can such an ideal competence be achieved in a space like the classroom? And how can one assert one’s identity while recognizing the Other? These are the questions this research seeks to address. The mondialisation affects all of the video domains, including the general sense-apprentissage. This imposes auxiliary sensibilities on revoiring different objects of sensing- apprentissage of different languages, large cells- that are conscientious of the visible vehicle or inconscient of the culture. Prepondérante in the processus d’enseignement- apprentissage, en revanche, on s’accorde also que son enseignement demeure difficile, du fait de son caractère polymorphe, dynamique et évolutif. Globalization affects all areas of life, especially teaching and learning in general. This requires teachers to review their teaching and learning objectives of foreign languages, especially when these are considered as the conscious or unconscious vehicle of a culture. Everyone actually agrees that culture now takes a predominant place in the teaching-learning process, on the other hand, we also agree that its teaching remains difficult, because of its polymorphous, dynamic and evolving character. Indeed, the avowed goal of each teacher is the following: the teaching of cultures can develop in its learners a cultural competence promoting intercultural communication between individuals of different cultures. - How to claim to achieve this ideal skill, in a space like the classroom? - How to assert your identity, while recognizing the other? These are the questions we seek to answer through this research